The conflict for the truth. Phenomenology and the future task of philosophy - Held, Klaus; Hoyos Vásquez, Guillermo (Estudios de Filosofía, 1996)
The very access lo phenomenology is, according lo Edmund Husserl, his father, the epoche or suspension of statements asserting beingfrom a fact. This suspension of preconceptions has been on the base of science and philosophy from their beginning. For Stoic and Sceptic philosophers in Hellenic period, epoche was based on other un examined presuppositions according to which, given the big gap between the existence of the facts and their appearance, it must befilled by means ofa decision of the will. It was from this conception that modern voluntarism, whose political and ecological consequences are the immediate concern of humanity nowadays, arase. Befare Hellenism, Greek thought had rested on the differentiation of appearance and being, without assigning a role to the will. In the new form of epoche within phenomenology both presuppositions are suppressed. So, appearing means becoming evident within a "horizon". After subjectivism, and in order to re-open the way for philosophy, the task of phenomenology is to clarify the sense in which the world is much more than a particular horizon, and to assume the implications of this. Only then, the relation between being and appearance as well as the meaning of will regarding the place of men in the world will become clear.